ANALISIS EFISIENSI DAN EFEKTIFITAS PENGELOLAAN ANGGARAN PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SINJAI - Hasdiana S Hasdiana S (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The results showed that the efficiency ratio analysis results showed that the average level of efficiency of budget management at the Department of Trade and Industry Sinjai during 2011 to 2015 was 41%, meaning efficient budget management implemented. The results of the analysis of the effectiveness ratio showed an average level of efficiency of budget management at the Department of Trade and Industry Sinjai during 2011 to 2015 was 87%, meaning effect budget management implemented.